Case Report: Successful Treatment With Monoclonal Antibodies in One APDS Patient With Prolonged SARS-CoV-2 Infection Not Responsive to Previous Lines of Treatment - Rivalta, Beatrice; Amodio, Donato; Giancotta, Carmela; Santilli, Veronica; Pacillo, Lucia; Zangari, Paola; Cotugno, Nicola; Manno, Emma Concetta; Finocchi, Andrea; Bernardi, Stefania; Colagrossi, Luna; Gentile, Leonarda; et al. (Frontiers in Immunology, 2022)
We described the case of a patient affected by Activated PI3K-kinase Delta Syndrome (APDS) and a long-lasting and pauci-symptomatic SARS-CoV-2 infection, treated with multiple therapeutic agents including Remdesivir, and SARS-CoV-2-neutralising monoclonal antibodies. We detected the clearance of the virus 105 days from the first positive swab, 7 days after monoclonal antibodies administration. At genotyping the SARS-CoV-2 virus resulted wild type on all samples tested. This case shows the monoclonal antibodies’ good tolerability and efficacy in reducing viral shedding in long-lasting infections refractory to other treatments.